Value of Cine Phase Contrast Magnetic Resonance Imaging to Predict Obstructive Hydrocephalus - Weinzierl, M.R.; Krings, T.; Ocklenburg, C.; Korinth, M.C. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2012)
Background This is a prospective study to evaluate the role of CINE MRI to predict obstructive hydrocephalus in the preoperative work-up.Patients/Material and Methods A total of 16 patients with aqueductal obstruction demonstrated by CINE MRI who were undergoing ETV were included. MRI was performed preoperatively, at 3 months, at 12 months and at 24 months after surgery. Prior to the fenestration of the third ventricular floor aqueductal patency was evaluated using intraoperative ventriculography. A successful outcome was defined by using radiological and clinical criteria.Results In 8 patients with aqueductal obstruction on preoperative CINE MRI aqueductal patency was proven intraoperatively. ETV failed in all patients with intraoperatively proven aqueductal patency. Out of these 8 patients, 1 patient had no risk factors for ETV failure, 3 had 1 risk factor, 3 had 2 risk factors, and 1 had 3 risk factors. Most of the failure (6 out of 8 patients) occurred within 8 weeks of the initial procedure. A lumbar puncture was performed in these patients to avoid misinterpretation of the clinical course.Conclusion The present study demonstrates that cine phase constrast MR may be a poorer choice to determine aqueductal patency compared to high resolution structural imaging. Interestingly, intraoperative ventriculography was an adjunct to better predict outcome after ETV in patients with obstructive hydrocephalus. In cases with non-conclusive preoperative imaging, postoperative decision making may be supported by the use of intraoperative ventriculography with the goal of reducing unnecessary tests and procedures. However, the analysis of the study data has to be considered as explorative. Therefore, findings should be validated with a larger patient population.
Keywords: obstructive hydrocephalus; third ventriculostomy; ventriculoperitoneal shunt; cine phase contrast MRI